The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1095-8649.2011.02974.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and contemporary population genetic connectivity of the European short‐snouted seahorse Hippocampus hippocampus and implications for management

Abstract: This first genetic study of Hippocampus hippocampus covers the species' entire geographic range and employs two mtDNA markers (control region and cytochrome b) to establish patterns of population structuring. A total of 255 specimens from 21 locations were used to obtain 89 concatenated haplotypes. The common haplotype was present in all but one population, however, most haplotypes were unique. The haplotype network had a star-like construction, suggesting expansion from a bottleneck event. F(ST) and AMOVA rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 74 publications
(76 reference statements)
2
50
0
Order By: Relevance
“…The range expansion was a recent phenomenon and may not have obtained the migration-drift equilibrium, as shown by the lack of phylogeographical structure [38]. A similar star-like pattern of genetic relatedness among haplotypes was seen in other seahorses, such as H. hippocampus (L. 1758) [49].…”
Section: Discussionmentioning
confidence: 86%
“…The range expansion was a recent phenomenon and may not have obtained the migration-drift equilibrium, as shown by the lack of phylogeographical structure [38]. A similar star-like pattern of genetic relatedness among haplotypes was seen in other seahorses, such as H. hippocampus (L. 1758) [49].…”
Section: Discussionmentioning
confidence: 86%
“…These findings are consistent with Woodall et al . (), who concluded that these expansions were probably affected by interglacial cycles in the late Pleistocene (190 to 21 ka). In addition, the Cape Verde frontal zone, where the southward‐flowing Canary Current begins to shift westwards, has been observed as a barrier to gene flow in several eastern Atlantic species, and may have contributed to the observed divergence (Vangriesheim et al ., ; Woodall et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results also support those of Woodall et al . (), who concluded that the West African population of H. hippocampus is genetically distinct from the European population. Like H. patagonicus , the West African population of H. hippocampus should also be considered a priority for conservation.…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning given that CITES documents annual exports of around 700 000 individuals (2004–2010; World Conservation Monitoring Centre, http://www.unep-wcmc.org), making this one of the most traded seahorse species. The short‐snouted seahorse Hippocampus hippocampus (L. 1758) also occurs in this region (Lourie et al , ; West, ), yet the only specimens attributed to West Africa (Senegal) in known analyses were obtained in Hong Kong markets (Woodall et al , ).…”
Section: Summary Statistics For Hippocampus Algiricus Hippocampus Himentioning
confidence: 99%